Brigham Young, pioneer prophet / Pioneer Prophet - Turner, John G (Cambridge, Massachusetts ; London, England : The Belknap Press of Harvard University Press, 2012)
Provides a comprehensive portrait of the Mormon spiritual leader, viewed by followers as a protector and by opponents as a heretic, and describes how his faith has impacted the Mormon religion for over a century.
A new creature -- The tongues of angels -- Acts of the apostles -- New and Everlasting Covenant -- Prophets and pretenders -- Word and will -- A new era of things -- One family -- Go ahead -- The whirlwind -- Let him alone -- The monster in the vale -- The soul and mainspring of the West.
Includes bibliographical references (pages 415-486) and index.
Keywords: Young, Brigham, -- 1801-1877.; Church of Jesus Christ of Latter-day Saints -- Presidents -- Biography; Mormon Church -- Presidents -- Biography